A Colorimetric/Ratiometric Fluorescent Probe Based on Aggregation-Induced Emission Effect for Detecting Hypochlorous Acid in Real Samples and Bioimaging Applications - Junliang Chen; Pingping Xiong; Huawei Niu; Weiwei Cao; Wenfen Zhang; Shusheng Zhang (Foods)
Hypochlorous acid (HClO) serves as a biological mediator and is widely utilized as a disinfectant in food processing and water treatment. However, excessive HClO residues in food and environmental water raise concerns due to the potential formation of carcinogenic chlorinated byproducts and disinfection byproducts (DBPs). Despite its importance, traditional methods for HClO detection often involve complex sample preparation, sophisticated instrumentation, and skilled operators. Herein, we report an aggregation-induced emission (AIE) small molecule fluorescent probe (NYV) that integrates colorimetric and ratiometric fluorescence responses for the detection of HClO. This probe exhibits high sensitivity, with a detection limit of 0.35 <semantics>μ</semantics>M, a rapid response time of 1 min, and a wide linear range (0–142.5 <semantics>μ</semantics>M), along with anti-interference capabilities, making it suitable for real-time monitoring. Furthermore, we have developed a portable solid-state sensor based on probe NYV for the rapid visual detection of HClO. The potential applications of this probe in real sample analysis and bioimaging experiments are demonstrated. Our findings contribute to the development of innovative fluorescent probes for HClO detection, with broad applications in food safety, environmental monitoring, and biomedical research on oxidative stress and ferroptosis.